The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/lary.26721
|View full text |Cite
|
Sign up to set email alerts
|

Can the Ni classification of vessels predict neoplasia? A systematic review and meta‐analysis

Abstract: Objectives: The Ni classification of vascular change from 2011 is well documented for evaluating pharyngeal and laryngeal lesions, primarily focusing on cancer. In the planning of surgery it may be more relevant to differentiate neoplasia from non-neoplasia. We aimed to evaluate the ability of the Ni classification to predict laryngeal or hypopharyngeal neoplasia and to investigate if a changed cutoff value would support the recent European Laryngological Society (ELS) proposal of perpendicular vascular change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
1
25
2
Order By: Relevance
“…The present diagnosis and classification using the NBI laryngoscope worldwide basically depends on the Ni classification. Meta‐analysis showed that the overall sensitivity of the laryngeal cancer diagnosis based on type V was 0.82 (95% confidence interval [CI]: 0.75–0.87) and the specificity was 0.93 (95% CI: 0.82–0.97) …”
Section: Discussionmentioning
confidence: 99%
“…The present diagnosis and classification using the NBI laryngoscope worldwide basically depends on the Ni classification. Meta‐analysis showed that the overall sensitivity of the laryngeal cancer diagnosis based on type V was 0.82 (95% confidence interval [CI]: 0.75–0.87) and the specificity was 0.93 (95% CI: 0.82–0.97) …”
Section: Discussionmentioning
confidence: 99%
“…There are other methods of microvessel morphological evaluation, aside from the JES classification. The Ni classification of vascular change, proposed in 2011, is probably one of the most well‐documented systems . The Ni classification aims to diagnose early HNSCCs based on microvessel morphological evaluation; however, the literature does not clarify whether the correspondence of the vessel type of Ni classification and the depth of tumor invasion was evaluated in precise.…”
Section: Discussionmentioning
confidence: 99%
“…The Ni classification of vascular change, proposed in 2011, is probably one of the most well-documented systems. [20][21][22] The Ni classification aims to diagnose early HNSCCs based on microvessel morphological evaluation; however, the literature does not clarify whether the correspondence of the vessel type of Ni classification and the depth of tumor invasion was evaluated in precise. To our knowledge, the types Va and Vb vessels of the Ni classification apparently correspond with the B1 and B2 vessels of the JES classification, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of superficial vascular patterns of the vocal folds has emerged in the last years as an important element in the diagnostic workup of vocal fold lesions, in addition to the evaluation of the mucosal surface or volume changes using conventional WLE and the evaluation of vibratory patterns using stroboscopy and high-speed imaging [15]. Modern image-enhancing technologies, such as NBI, SPIES, or i-SCAN, and the technical evolution of endoscopes, which nowadays enable a high image resolution up to 4K, allow a detailed description of minute mucosal and vascular changes [7]. As a result, nonspecific termini such as erythroplakia should be replaced through more precise descriptions of mucosal and vascular patterns [6], leading to increases in the accuracy and reproducibility of endoscopic diagnostics in preoperative and intraoperative settings [3,[16][17][18].…”
Section: Endoscopic Evaluation Of Vascular Patterns Of the Vocal Foldsmentioning
confidence: 99%
“…Changes in the morphology and three-dimensional spread of vocal fold vessels result from various functional, mechanical, or neoplastic stimuli and have been associated with the development of benign or malignant laryngeal pathologies, such as recurrent respiratory papillomatosis or laryngeal carcinoma [1][2][3]. Several classification systems have been proposed to describe and categorize subepithelial and epithelial vascular changes, while different image-enhancing technologies (electronic chromoendoscopy), such as narrow-band imaging (NBI), Storz professional image enhancement system (SPIES), or i-SCAN, have been used to ease their detection [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%